Transitioning from LPN/LVN to BSN - Duphily, Nancy (Springer Publishing Company, LLC, 2014)
"Programs that address the transition from practical/vocational nursing to Baccalaureate nursing were virtually nonexistent two years ago; today there are 155 such programs, a number that continues to increase. This is the first text to address the specific educational needs of students transitioning from LPN/LVN to BSN and professional practice. Comprehensive and user-friendly, the text covers every aspect of role transition in the LPN/LVN to BSN course. It is based on the recommendations of the Institute of Medicine's 'Future of Nursing' and the 'BSN in 10' initiative. The book provides an overview of professional practice at the BSN level and examines the core, role, and skill competencies required for the Baccalaureate-prepared nurse. The text addresses competence in leadership and management, critical thinking, cultural intelligence, information technology, and professional writing, as well as legal and ethical concerns. It focuses on the role of the RN within an interdisciplinary team, describes the experience of returning to an academic setting, and the challenges of and strategies for accomplishing a successful role transition. Numerous reflective exercises, case vignettes and online case studies reinforce content. Important practice concepts like QSEN and the Essentials of Baccalaureate Education for Professional Nursing Practice are woven throughout the text. A robust ancillary package includes PowerPoints, online quizzes, reflective questions, and case studies"--Provided by publisher